Los cuentos tridimensionales en el desarrollo de la inteligencia lingüística en los niños y niñas de 4 a 5 años de edad en la Unidad Educativa “Santa Mariana de Jesús Martínez Barba” en el cantón Chimbo, provincia de Bolívar en el período 2023 - Males Mendez, Jeniffer Yajaira (2023)
Linguistic intelligence faces problems that arise in the Educational Unit "Santa Mariana de Jesús Martínez Barba", due to the lack of the use of three- dimensional stories, which help in learning to read in children. The research focuses on collecting the information necessary to analyze and interpret the results. The observation sheet was applied to 31 people, both boys and girls and the teacher, with the results obtained we were able to identify the lack of linguistic intelligence in infants, the lack of interest on the part of the teacher to implement and elaborate three-dimensional stories. The realization of the three-dimensional stories helped the boys and girls to improve their vocabulary, managing to positively develop linguistic intelligence. Finally, different solution alternatives were proposed to improve learning